The women’s knowledge about the urinary incontinence and ways of controlling the illness - Derewiecki, Tomasz; Duda, Marta; Majcher, Piotr; Mroczek, Krzysztof (Polish Journal of Public Health, 2012)
Introduction. The urinary incontinence (UI) is considered one of the most often occurring chronic diseases in wo-men. It consists in uncontrolled leakage of urine through the urethra. It concerns 17-60% of the female population. Aim. The main aim of the present work was to investigate women’s knowledge about the problem of urinary incontinence and its practical application dealing with the problem, what would contribute to improving the quality of life. Material and methods. There were 101 female patients surveyed from the Zamość Rehabilitation Center of University of Management and Administration. The population was diversified with regard to age, place of living and education. The age of the examined women varied from 30 to 87 years. The research tool used was an author`s questionnaire survey. In the statistical analysis of the results Microsoft Excel program was applied. The significance level was accepted for p<0.05. Results. For 69.31% respondents it was the embarrassing problem, but for 30.69% it was not. According to 35.64% women the age is the factor which influences UI to the highest degree. Next are the previous pregnancies (27.72%), hard physical labor (12.87%), frequent infections of the urinary tract (11.88%), genetic factors (8.91%), and excess weight (2.97%). The methods of dealing with the problem which respondents list most frequently are: exercises (37.62%), using of inserts/ sanitary towels (27.72%), pharmacotherapy (13.86%), operation (10.89%), avoiding effort (1.98%), frequent emptying, Botox, limiting consumption of drinks (0.99%). Conclusions. In the opinion of the investigated women, UI was an embarrassing illness, often concealed, so the availability of information should be easier, both in urban and in rural areas. In both tested groups the respondents stated that UI exerted a negative influence on different spheres of life and on a quality of life, so it should be emphasized here that it is a social-economic problem. The tested women knew different methods of dealing with UI, but they didn`t know about such non-invasive methods as electrotherapy or biofeedback therapy. The women especially exposed to UI were those who were multipara. That is why a thoroughly prepared informing program about UI should be conducted among those women.